Assessment of Rare Cancers and Sarcoma Policy and Sarcoma Drug Approvals in Latin America: A Report From the LACOG Sarcoma Group - Douglas Dias e Silva; Bruna Bianca Lopes David; Veridiana Pires de Camargo; Renee Zon Filipi; María Lucila González Donna; Juan Carlos Haro Varas; Rodrigo Ramella Munhoz; Maycos L. Zapata; Cicero Luiz Cunha Martins; Matias Chacon; Rafael Schmerling; Reynaldo Jesus Garcia; et al. (JCO Global Oncology, 2025)
PURPOSEThe availability of drugs and national public policies for patients with rare cancers, including sarcomas, varies in different parts of the world.METHODSIn this manuscript, we have conducted a comprehensive analysis to evaluate rare cancer policies in Latin American countries' national policy documents. Additionally, we have reviewed the approvals for sarcoma drugs in selected Latin American countries and compared them with US Food and Drug Administration (FDA) and European Medicines Agency (EMA) approvals.RESULTSThe documents reviewed showed a lack of explicit focus on rare cancers, with no mention in 70% of the countries analyzed. Drug approval data reveal that in the last 15 years, the FDA and EMA have approved 19 and 13 drugs for sarcoma, whereas their Latin American counterparts, namely ANVISA, ANMAT, and COFEPRIS, approved six, eight, and seven drugs, respectively.CONCLUSIONOur data suggest that improving rare cancer and sarcoma care in Latin America requires enhanced collaboration for better rare cancer policies.